Ultrathin buried resistance copper foil and preparation process and application thereof
By preparing a peelable layer on the carrier copper foil and subjecting electroplating, the problem of vulnerability of the resistive layer in the ultra-thin buried copper foil is solved, the accuracy and stability of the resistance value are improved, the process flow is simplified and the basis and The bonding force of the material layer.
Patent Information
- Application Number
- CN202411452584.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-01-03
AI Technical Summary
The existing embedded resistive copper foil is easily damaged during the etching process, resulting in unstable resistance value and poor accuracy, especially in ultra-thin copper foil, which affects the design of resistance value and resistance change ability. .
By preparing a peelable layer, including an organic layer and a metal layer, electrolytic deposition and etching, forming an ultrathin copper foil, and electroplating resistance layer treatment on its surface, followed by silanization to enhance the substrate with The bonding force of the layer is finally obtained by mechanical peeling to obtain ultra-thin buried copper foil.
Improve the integrity and stability of the resistor layer, enhance the accuracy of the resistance value, simplify the process flow, clearly distinguish between copper foil and resistance areas, reduce the surface roughness and risk of fracture of the resistor layer, and improve the base material layer Binding strength.
Smart Images

Figure CN119252588A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of PCB manufacturing, and relates to an ultra-thin buried barrier copper foil, and in particular to an ultra-thin buried barrier copper foil and a preparation process and application thereof. Background Art
[0002] The surface of traditional PCB (printed circuit board) is often covered with resistor components, which not only takes up a lot of board space, but also affects the decoupling effect of signal transmission impedance due to the presence of vias and wires, which may cause integrity problems of transmission line signals. In order to solve this problem, embedded resistor technology came into being and became the key to the integration of resistor devices.
[0003] Embedded resistor copper foil is a new material formed by combining resistors with copper foil. The thin film resistor material is pressed onto a special semi-cured resin board, etched to form a thin film resistor, and then laminated into the printed circuit board. Embedded resistor copper foil embeds a large number of passive component resistors that can be embedded directly into the high-frequency and high-speed PCB board, significantly shortening the line length between components, effectively improving electrical characteristics, and increasing the packaging area utilization of the PCB board. This technology also reduces the number of solder joints on the PCB board, thereby improving the reliability of the package and reducing production costs.
[0004] The invention patent with publication number CN103643085A discloses an embedded thin film resistor material and a preparation method thereof. The embedded thin film resistor material includes 50-76% nickel, 10-18% chromium, 10-30% carbon and 0.5-5% tungsten in atomic percentage. Nickel, chromium, carbon and tungsten atoms are deposited on a copper foil substrate by magnetron sputtering technology to obtain a nickel-chromium-carbon-tungsten thin film.
[0005] The invention patent with publication number CN105695993B discloses a method for preparing an embedded resistor copper foil, comprising the following steps: on the upper and lower surfaces of a whole piece of thermoplastic polymer film, a metal copper layer is formed by chemical copper deposition and electroplating, and a resistor nickel-phosphorus alloy layer is formed by chemical nickel plating; the edges and corners of the material obtained in the previous step are cut to expose the thermoplastic polymer film; the thermoplastic polymer film in the material obtained in the previous step is dissolved by an organic solvent to remove it; the material obtained in the previous step is cleaned and dried to finally obtain two embedded resistor copper foils.
[0006] The invention patent with publication number CN116056344A discloses a production process for embedded resistor copper foil, comprising: (1) performing nodularization treatment on the smooth surface of the original foil; (2) coating the surface of the original foil treated in step (1) with an organic isolation passivation liquid; the organic isolation passivation liquid comprises an organic film-forming agent, an inorganic passivating agent, an additive and deionized water; the organic film-forming agent is selected from acrylic resin and / or polyurethane resin; the inorganic passivating agent is selected from vanadyl sulfate and / or titanyl sulfate; (3) electroplating nickel alloy on the surface of the original foil treated in step (2); (4) performing high-temperature pressing on the original foil treated in step (3) using a PTFE substrate, and finally obtaining the embedded resistor copper foil by full-plate etching.
[0007] Buried resistor copper foil is one of the key materials for embedded resistor technology. Currently, the more conventional buried resistor copper foil is prepared by forming a coating with specific resistance properties on the surface of the copper foil through electroplating, chemical plating or sputtering.
[0008] Embedded resistor technology brings many advantages to PCB design, but it is also accompanied by certain challenges. When the buried resistor copper foil is used in the downstream PCB board, it usually needs to go through: film-exposure-development-etching to remove the copper layer of the non-circuit pattern → etching to remove the resistor layer of the non-circuit pattern → film stripping-film-film-exposure-development-etching to remove the copper layer in the circuit pattern to expose the buried resistor pattern-film stripping. After the above steps are completed, a circuit with a resistor function is usually obtained, and the process is relatively complicated. The buried resistor copper foil prepared by forming a resistor layer on the surface of this copper foil often has a thin resistor layer thickness of only 0.1-1μm. The buried resistor function circuit formed by multiple etchings needs to undergo multiple pressing and etching in the production of PCB boards, which is easy to cause the thickness of the resistor layer to change, and even the resistor layer to deform and break, affecting the size and accuracy of the resistance value. For ultra-thin copper foil (3μm≤5μm) with poor resistance to deformation, the impact is greater; and after the buried resistor copper foil is etched to expose the buried resistor pattern, there is still a resistor layer under the copper foil, which will also affect the design of the size and accuracy of the resistance value of the buried resistor pattern.
[0009] Since the buried resistor layer is relatively thin, it is easy to cause the thickness of the resistor layer to change, deform or even break during multiple etching processes, affecting the stability and accuracy of the resistance value. In addition, after etching, the ultra-thin copper foil exposes the resistor pattern, and the resistor layer still exists under the copper foil, which also affects the design accuracy of the resistor value. Further improvements are needed to address the above problems. Summary of the invention
[0010] The present invention aims at the problems existing in the prior art and provides an ultra-thin buried resistive copper foil and its preparation process and application. By introducing a peelable layer, the integrity and stability of the resistive layer can be ensured, and a composite copper foil layer is obtained by etching and preparing the resistive layer on the surface of the ultra-thin copper foil layer, and a silanization treatment is performed on the surface of the composite copper foil layer to enhance the bonding force with the downstream substrate layer, thereby solving the problem that the resistive layer is easily damaged in the traditional process and improving the accuracy of the resistance value.
[0011] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0012] In a first aspect, the present invention provides a process for preparing an ultra-thin buried barrier copper foil, comprising the following steps:
[0013] (1) Pretreatment of carrier copper foil;
[0014] (2) preparing a peelable layer; the peelable layer comprises an organic layer and a metal layer; the two sides of the organic layer are respectively a carrier copper foil and a metal layer; the organic layer is a polydopamine layer;
[0015] (3) preparing an ultra-thin buried barrier copper foil; performing electrolytic deposition on the surface of the metal layer to obtain an ultra-thin copper foil layer; performing etching on the ultra-thin copper foil layer and electroplating a resistor layer to obtain an ultra-thin buried barrier copper foil layer after electroplating, and removing the carrier copper foil and the strippable layer to obtain the ultra-thin buried barrier copper foil.
[0016] The carrier copper foil pretreatment in step (1) is specifically as follows: the carrier copper foil is pretreated with an alkaline solution, preferably, the temperature of the alkaline solution is 40-50° C., and the alkaline solution is KOH, NaHCO in a concentration ratio of 3-1:1. 3 ethanol aqueous solution; in the ethanol aqueous solution, the volume ratio of ethanol to water is 1:1.
[0017] In one embodiment, the carrier copper foil pretreatment is specifically as follows: first, the carrier copper foil is unwound, and the unwinding speed of the carrier copper foil is 0.1-5 m / min. After unwinding, the carrier copper foil is preferably pretreated with an alkaline solution, and the temperature of the alkaline solution is 40-50° C. Preferably, the alkaline solution is KOH, NaHCO with a concentration ratio of 3-1:1. 3 wherein the volume ratio of ethanol to water is 1:1. In one embodiment, the thickness of the carrier copper foil is 18-35 μm.
[0018] After the pretreatment, the carrier copper foil is preferably washed with water, wherein ultrapure water is used for washing, the washing temperature is 25-35° C., and the washing flow rate is 10-30 mL / s.
[0019] The step (2) of preparing the strippable layer specifically comprises: then preparing an organic layer on one side of the carrier copper foil to obtain a carrier copper foil loaded with an organic layer. The organic layer is a polydopamine layer, and the polydopamine layer is obtained by self-polymerization of a dopamine alkaline solution. The dopamine alkaline solution is a Tris buffer solution containing 1-4 mg / L dopamine and a pH value of 8-9. In one embodiment, the step of preparing the organic layer specifically comprises: spraying a dopamine alkaline solution on one side of the carrier copper foil, the dopamine alkaline solution is a Tris buffer solution containing 1-4 mg / L dopamine and a pH value of 8-9, and the dopamine alkaline solution undergoes self-polymerization on one side of the carrier copper foil to obtain an organic layer. The preparation of the organic layer utilizes the self-polymerization reaction of dopamine in an alkaline environment to form a polydopamine coating on the surface of the carrier copper foil.
[0020] After preparing the organic layer on one side of the carrier copper foil, it is preferably washed with water, wherein ultrapure water is used for washing, the washing temperature is 25-35°C, and the washing flow rate is 10-30mL / s, and then a metal layer is prepared on the surface of the organic layer to obtain a carrier copper foil loaded with a peelable layer, wherein the peelable layer includes an organic layer and a metal layer; and the two sides of the organic layer are carrier copper foil and a metal layer, respectively. The metal layer is obtained by electroplating a metal plating solution, and preferably, the metal plating solution includes: 1.2-1.6g / L nickel sulfate, 0.6-0.8g / L zinc sulfate, 2.4-3.2g / L boric acid, 60-70g / L potassium pyrophosphate, 24-32mg / L saccharin sodium and water; the water is used as a solvent, preferably ultrapure water. Preferably, the pH value of the metal plating solution is 8-9.
[0021] After the carrier copper foil carrying the peelable layer is obtained, it is preferably washed with water, wherein ultrapure water is used for washing, the washing temperature is 25-35° C., and the washing flow rate is 10-30 mL / s.
[0022] The step (3) of preparing the ultra-thin buried copper foil specifically comprises: firstly, using the electrolytic deposition of copper foil electrolyte to prepare an ultra-thin copper foil layer on the surface of the metal layer. The copper foil electrolyte comprises the following components: Cu 2+ 50-65g / L, sulfuric acid 90-130g / L, Cl - 6-10 mg / L, 30-40 mg / L of hydrolyzed collagen with a molecular weight of 2000-3000 Da and 15-20 mg / L of sodium polydisulfide propane sulfonate. The electrolytic temperature of the electrolytic copper foil deposition electrolyte is 43-47°C, and the electrolytic current density is 300-500 mA / cm 2 .
[0023] After the ultra-thin copper foil layer is prepared, it is preferably washed and dried. The washing is performed with ultrapure water, the washing temperature is 25-35°C, and the washing flow rate is 10-30mL / s. The drying temperature is 130-140°C. The ultra-thin copper foil layer is etched to obtain a resistance window, and the etching is performed with an etching solution, which is a conventional acidic copper chloride or alkaline copper chloride solution on the market that can quickly etch copper foil, and is not limited here. Preferably, the etching solution is an acidic copper chloride solution, and the etching solution contains the following components: 90-110 g / L copper ions and 100-120 g / L chloride ions; the pH value of the etching solution is preferably 2-4, and the temperature of the etching solution is 45-55°C; the resistor electroplating solution includes nickel salt, chromium salt, sodium hypophosphite and boric acid; in the resistor electroplating solution, the concentration of nickel ions in the nickel salt is 20-30 g / L, the concentration of chromium ions in the chromium salt is 4-8 g / L, the concentration of sodium hypophosphite is 20-26 g / L, and the concentration of boric acid is 20-24 g / L; the electroplating temperature of the resistor electroplating solution is 48-52°C; the electroplating current density of the resistor electroplating solution is 150-400 A / dm 2 The lower the concentration of nickel, chromium and hypophosphorous acid in the resistor electroplating solution, the greater the electroplating current density of the resistor electroplating solution, the easier it is to form fine grains, and the greater the resistivity of the resistor formed.
[0024] After etching the exposed ultra-thin copper foil to form a resistance window using an etching solution, water washing is preferably performed, wherein ultrapure water is used for the water washing, the water washing temperature is 25-35° C., and the water washing flow rate is 10-30 mL / s.
[0025] After etching the ultra-thin copper foil layer to obtain a resistor window, a resistor electroplating solution is used to electroplate the resistor window to prepare a resistor layer, thereby obtaining an ultra-thin buried resistor copper foil layer after electroplating. The resistor electroplating solution includes nickel salt, chromium salt, sodium hypophosphite and boric acid. Preferably, in the resistor electroplating solution, the concentration of nickel ions in the nickel salt is 20-30g / L, the concentration of chromium ions in the chromium salt is 4-8g / L, the concentration of sodium hypophosphite is 20-26g / L, and the concentration of boric acid is 20-24g / L. The electroplating temperature of the resistor electroplating solution is 48-52°C, and the electroplating current density of the resistor electroplating solution is 150-400A / dm 2 After obtaining the ultra-thin buried copper foil layer after electroplating, it is preferably washed with water, wherein ultrapure water is used for washing, the washing temperature is 25-35° C., and the washing flow rate is 10-30 mL / s.
[0026] In one embodiment, the steps of preparing the ultra-thin copper foil layer and the resistor layer in step 3) can be repeated multiple times by setting multiple grooves, so as to increase the thickness or cross-sectional area of the ultra-thin buried resistor copper foil or the resistor layer. For example: passing through two ultra-thin copper foil aqueducts, the ultra-thin copper foil is electrodeposited twice; passing through three resistor windows, the resistor is deposited three times.
[0027] After preparing the ultra-thin buried barrier copper foil layer after electroplating on the surface of the organic layer, it is preferred to perform silanization treatment on the surface of the ultra-thin buried barrier copper foil layer, and the silanization treatment refers to spraying an organic silane coupling agent on the surface of the ultra-thin buried barrier copper foil layer to be bonded to the downstream substrate to increase the adhesion between the ultra-thin buried barrier copper foil layer and the downstream substrate. The organic silane coupling agent is selected from one or more of KH550, KH560 and KH570. The concentration of the organic silane coupling agent in the silanization treatment is 1.0-1.5g / L, the pH value is 9-12, and the temperature is 25-35°C. After the silanization treatment, it is preferably dried, and the drying temperature is 130-140°C. After the silanization treatment is performed on the surface of the ultra-thin buried barrier copper foil layer, the carrier copper foil and the strippable layer are removed to obtain the ultra-thin buried barrier copper foil.
[0028] In one embodiment, after the surface of the ultra-thin buried copper foil layer is silanized, a substrate layer is prepared, and the substrate layer is prepared by pressing and curing a semi-cured sheet on the surface of the ultra-thin buried copper foil layer treated with silanization, and the semi-cured sheet is preferably pressed and cured at 180°C for 1 hour. Silanization treatment is performed on the surface of the ultra-thin buried copper foil layer to improve the bonding strength between the ultra-thin buried copper foil layer and the downstream semi-cured sheet. Then, a mechanical stripping method is used to remove the carrier copper foil and the peelable layer to obtain an ultra-thin buried copper foil loaded with a semi-cured sheet, which is applied to a buried PCB board. The ultra-thin buried copper foil can be etched downstream respectively with an ultra-thin copper foil layer and an electroplated resistor layer to achieve a more accurate circuit design.
[0029] Preferably, the step (3) further comprises film unwinding, laminating, peeling and winding, specifically: unwinding the film with the window and laminating it on the surface of the ultra-thin copper foil layer, then etching the ultra-thin copper foil layer exposed at the window position of the film, and electroplating to obtain an ultra-thin buried barrier copper foil layer, peeling the film and the ultra-thin buried barrier copper foil layer after electroplating and winding, removing the carrier copper foil and the peelable layer, and obtaining the ultra-thin buried barrier copper foil. The film unwinding and winding speed is preferably 0.1-5m / min, more preferably 0.1-2, and more preferably 1m / min.
[0030] In one embodiment, a film with a window is unwound and pressed by a pressure roller to fit tightly to the surface of the ultra-thin copper foil layer. The speed of the film unwinding is the same as the speed of the carrier copper foil unwinding, which is 0.1-5m / min. Then, an etching solution is used to etch the ultra-thin copper foil exposed at the window position of the film to form a resistance window. The etching solution is a conventional acidic copper chloride or alkaline copper chloride solution on the market that can quickly etch copper foil, which is not limited here. Preferably, the etching solution contains: a copper ion concentration of 90-110g / L and a chloride ion concentration of 100-120g / L; the pH value of the etching solution is 2-4, and the temperature of the etching solution is 45-55°C, which can provide a faster etching rate. The position and size of the film window are consistent with the position and size of the resistance window of the ultra-thin copper foil. The position of the resistance window of the ultra-thin copper foil is designed according to the position of the required ultra-thin buried copper foil, and the size of the resistance window is calculated according to the resistance value of the required ultra-thin buried copper foil. Then, the position and size of the film window are made according to the position and size of the resistance window of the ultra-thin copper foil. The calculation formula of the size of the resistance window is:
[0031] Resistance window length = resistance value × resistance window width × copper foil thickness ÷ resistivity of designed resistance layer;
[0032] For example, if you need to design a buried resistor with a resistance value of 25Ω, a line width of 1.0mm, and a thickness of 3μm, you can calculate that: resistance window length = resistance value × resistance window width × copper foil thickness ÷ resistivity of designed resistor layer = 25Ω × 1.0mm × 3μm ÷ (3 × 10 -5 Ω·m)=2.5mm. That is, the size of the resistance window is 2.5mm long and 1.0mm wide.
[0033] Then, etching is performed on the ultra-thin copper foil layer exposed at the window position of the film, and electroplating is performed to obtain an ultra-thin buried barrier copper foil layer after electroplating, and the film and the ultra-thin buried barrier copper foil layer are peeled off and rolled up. Preferably, a peeling roller is used to peel the film and the ultra-thin buried barrier copper foil layer. The winding speed is the same as the film unwinding speed in step 2), which is 0.1-5m / min. Preferably, the film is peeled off and rolled up from the ultra-thin buried barrier copper foil layer by a peeling roller, and then the carrier copper foil and the peelable layer are removed to obtain an ultra-thin buried barrier copper foil.
[0034] In the second aspect, the present invention provides an ultra-thin buried resistance copper foil prepared by the preparation process described in the above technical scheme, wherein the thickness of the ultra-thin buried resistance copper foil is 3-5μm, preferably 3-4μm, and more preferably 3μm; the roughness of the smooth surface is ≤1.5μm; the square resistance value is 20-50Ω / sq; and the square resistance value deviation is less than or equal to 10%.
[0035] In a third aspect, the present invention provides an ultra-thin buried barrier copper foil prepared by the preparation process described in the above technical scheme or an application of the ultra-thin buried barrier copper foil described in the above technical scheme in a buried barrier PCB board.
[0036] Compared with the prior art, the present invention has the following beneficial effects:
[0037] Firstly, the present invention prepares an organic layer and a metal layer on one side of a carrier copper foil (thickness 18-35 μm) to obtain a strippable layer, and prepares an ultra-thin buried barrier copper foil (thickness 3-5 μm) on the surface of the strippable layer. The thicker carrier foil provides effective support for the ultra-thin copper foil, and the carrier foil can be removed by mechanical stripping after the downstream pressing plate, which is easy to use.
[0038] Secondly, the present invention utilizes the self-polymerization reaction of dopamine to form an organic layer composed of polydopamine on the surface of the carrier copper foil, and the conductivity of polydopamine can be significantly improved by electro-depositing a metal layer of zinc-nickel alloy on the surface of the organic layer. By preparing a strippable layer on the carrier copper foil, the good conductivity of the strippable layer is conducive to improving the process and performance of the ultra-thin copper foil layer prepared by subsequent electrolytic deposition, and is conducive to forming a large current, and increasing the formation rate of the ultra-thin copper foil layer with a thickness of 3-5μm; it can make the current of electrolytic deposition more uniform, and the prepared ultra-thin copper foil layer is more controllable, uniform, and pinhole-free; it provides a large current density, promotes the formation of fine grains in the ultra-thin copper foil layer, and then improves the mechanical strength of the ultra-thin copper foil layer and reduces the surface roughness of the ultra-thin copper foil layer; it can also make the bonding force and peeling force between the carrier copper foil and the ultra-thin copper foil adaptable.
[0039] Thirdly, the present invention etches the ultra-thin copper foil layer to obtain a resistor window, and then prepares a resistor layer in the resistor window to obtain a composite copper foil layer, which is then silanized and dried, and finally pressed to remove the strippable layer to obtain an ultra-thin buried resistor copper foil. The process is simple, and the copper foil and the resistor area can be clearly distinguished. When in use, there is no resistor layer under the ultra-thin copper foil layer, and the size design of the resistor layer can be more accurate downstream.
[0040] Fourthly, the present invention pre-treats the carrier copper foil, so that the polydopamine layer formed on the surface of the carrier foil can be more uniform during the subsequent preparation of the organic layer composed of polydopamine, thereby improving the performance of the ultra-thin copper foil layer prepared by subsequent electrolytic deposition.
[0041] Fifthly, the ultra-thin buried copper foil provided by the present invention has a thickness of 3-5 μm, a smooth surface roughness of ≤1.5 μm, a square resistance of 20-50 Ω / sq, and a square resistance deviation of less than or equal to 10%. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 It is a schematic diagram of buried copper foil and its use in the prior art;
[0043] Figure 2The figure is a process flow chart for preparing ultra-thin buried barrier copper foil;
[0044] Figure 3 Schematic diagram of the copper foil in each process of ultra-thin buried barrier copper foil. DETAILED DESCRIPTION
[0045] It is worth noting that, unless otherwise specified, the raw materials used in the present invention are all common commercially available products, and their sources are not specifically limited.
[0046] Example 1
[0047] The buried copper foil used in the prior art is as follows Figure 1 As shown, Figure 1 It is a schematic diagram of buried copper foil and its use in the prior art. Figure 1 It shows that in the prior art, the buried barrier copper foil is composed of a resistor layer and a copper foil layer from bottom to top, or the buried barrier copper foil is composed of a substrate layer, a resistor layer and a copper foil layer from bottom to top.
[0048] The preparation process flow chart of the ultra-thin buried barrier copper foil provided by the present invention and the schematic diagram of the copper foil in each process are respectively as follows: Figure 2-3 As shown, the specific process flow of preparing ultra-thin buried copper foil is as follows:
[0049] (1) Pretreatment of carrier copper foil: First, unwind the carrier copper foil with a thickness of 18 μm (i.e., the carrier copper foil layer, Figure 3 As shown in A in the figure, the carrier copper foil is unrolled at a speed of 1 m / min. After unrolling, the carrier copper foil is pretreated with an alkaline solution, the temperature of the alkaline solution is 45° C., and the alkaline solution is KOH and NaHCO with a concentration ratio of 2:1. 3 ethanol aqueous solution; in the ethanol aqueous solution, the volume ratio of ethanol to water is 1:1.
[0050] After the carrier copper foil is pretreated, it is washed 1 with ultrapure water. The temperature of the water washing 1 is 30° C. and the flow rate of the water washing 1 is 20 mL / s.
[0051] (2) Preparing a peelable layer: preparing an organic layer on one side of a carrier copper foil, wherein the organic layer is prepared by spraying a dopamine alkaline solution on one side of the carrier copper foil, wherein the dopamine alkaline solution is a Tris buffer solution containing 2 mg / L dopamine and a pH value of 8.5, and the dopamine alkaline solution undergoes a self-polymerization reaction on one side of the carrier copper foil to obtain an organic layer composed of polydopamine.
[0052] After preparing an organic layer on one side of the carrier copper foil, ultrapure water is used for water washing 2, the temperature of water washing 2 is 30°C, the flow rate of water washing 2 is 20mL / s, and then a metal layer is prepared on the surface of the organic layer, and the metal layer is electroplated on the surface of the organic layer with a metal plating solution. Preferably, the metal plating solution is: 1.4g / L nickel sulfate, 0.7g / L zinc sulfate, 3.0g / L boric acid, 66g / L potassium pyrophosphate, 28mg / L saccharin sodium and water, and the pH value of the metal plating solution is 8.4.
[0053] After the metal layer is prepared, it is washed with ultrapure water for 3 times, the temperature of the water washing 3 is 30° C., and the flow rate of the water washing 3 is 20 mL / s, to obtain a peelable layer located on one side of the carrier copper foil, such as Figure 3 As shown in B.
[0054] (3) Preparation of ultra-thin buried copper foil: First, electrolytic deposition of copper foil electrolyte is performed, and the copper foil electrolyte has the following components: Cu 2+ 65g / L, sulfuric acid 90g / L, Cl - 6mg / L, 30mg / L of hydrolyzed collagen with a molecular weight of 2000-3000Da and 20mg / L of sodium polydisulfide dipropane sulfonate. The electrolysis temperature of the electrolytic copper foil deposition electrolyte is 47°C, and the electrolysis current density is 500mA / cm 2 An ultra-thin copper foil layer with a thickness of 3 μm is prepared on the surface of the metal layer. Figure 3 As shown in C.
[0055] After the ultra-thin copper foil layer is prepared, it is washed with ultrapure water 4, the washing temperature is 30°C, and the washing flow rate is 20mL / s. Then it is dried 1, and the drying temperature is 130°C. Then the film with a window is unwound. The speed of the film unwinding is the same as the speed of the carrier copper foil unwinding, which is 1m / min. Through the rolling of the pressing roller, the film is closely attached to the surface of the ultra-thin copper foil layer, such as Figure 3 As shown in D.
[0056] Furthermore, an etching solution is used to etch the ultra-thin copper foil exposed at the window position of the film to form a resistance window. The etching solution is a conventional alkaline copper chloride solution on the market that can quickly etch copper foil. The copper ion concentration in the etching solution is 90g / L and the chloride ion concentration is 100g / L. The pH value of the etching solution is 4.0, and the temperature of the etching solution is 50°C, which can provide a faster etching rate. The position and size of the window of the film are consistent with the position and size of the resistance window of the ultra-thin copper foil. The resistance window position of the ultra-thin copper foil is designed according to the position of the required ultra-thin buried copper foil, and the size of the resistance window is calculated according to the resistance value (25Ω) of the required ultra-thin buried copper foil. The calculation formula for the size of the resistance window is:
[0057] Resistance window length = resistance value × resistance window width × copper foil thickness ÷ designed resistance layer resistivity = 25Ω × 1.0mm × 3μm ÷ (3 × 10 -5 Ω·m)=2.5mm.
[0058] The position and size of the film window are made according to the position and size of the resistance window of the ultra-thin copper foil (length 2.5mm, width 1.0mm). The resistance window is etched on the exposed ultra-thin copper foil using etching liquid, such as Figure 3 As shown in E, ultrapure water is then used for washing, the washing temperature is 30° C., and the washing flow rate is 20 mL / s.
[0059] Furthermore, a resistor layer is prepared by electroplating at the resistor window using a resistor plating solution, such as Figure 3 As shown in F, an ultra-thin buried copper foil layer after electroplating is obtained. The resistor electroplating solution is composed of 24g / L nickel ions, 6g / L chromium ions, 24g / L sodium hypophosphite and 22g / L boric acid. The electroplating temperature of the resistor electroplating solution is 50°C and the electroplating current density is 300A / dm 2 After the resistor layer is formed by electroplating, it is washed with ultrapure water at a temperature of 30°C and a flow rate of 20 mL / s.
[0060] Then, a stripping roller is used to strip the film from the ultra-thin buried copper foil layer after electroplating. Figure 3 As shown in G, the film is rolled up, and the speed of the rolling up is the same as the speed of the film unwinding in step (3). Then, the surface of the ultra-thin copper foil layer after electroplating is subjected to silanization treatment, and an organic silane coupling agent is sprayed to increase the adhesion between the buried copper foil and the substrate. The organic silane coupling agent is KH550, with a concentration of 1.0 g / L, a pH value of 9, and a temperature of 30°C. After the silanization treatment, it is dried at 130°C.
[0061] Furthermore, the surface of the ultra-thin buried copper foil layer is laminated with a prepreg (epoxy resin), and pressed at 180°C for 1 hour for curing, and a substrate layer is prepared on the surface of the ultra-thin buried copper foil layer (i.e., ultra-thin buried copper foil with a thickness of 3 μm). Then, a mechanical stripping method is used to remove the carrier copper foil and the strippable layer to obtain an ultra-thin buried copper foil, such as Figure 3 As shown in H, the ultra-thin buried copper foil layer is composed of an ultra-thin copper foil layer and a resistor layer. According to the design requirements, the excess copper foil and the resistor layer are etched away to obtain the required circuit with resistor function (buried resistor PCB board). Figure 3 As shown in I.
[0062] Example 2
[0063] An ultra-thin buried barrier copper foil was prepared according to the preparation process of the ultra-thin buried barrier copper foil in Example 1. The difference from Example 1 is that "the dopamine alkaline solution is a Tris buffer solution containing 2 mg / L dopamine and a pH value of 8.5" is replaced by "the dopamine alkaline solution is a Tris buffer solution containing 4 mg / L dopamine and a pH value of 9", and "1.4 g / L nickel sulfate, 0.7 g / L zinc sulfate, 3.0 g / L boric acid, 66 g / L potassium pyrophosphate, 28 mg / L saccharin sodium and water, and the pH value of the metal plating solution is 8.4" is replaced by "the metal plating solution is: 1.6 g / L nickel sulfate, 0.8 g / L zinc sulfate, 3.2 g / L boric acid, 70 g / L potassium pyrophosphate, 32 mg / L saccharin sodium and water, and the pH value of the metal plating solution is 9" to obtain an ultra-thin buried barrier copper foil and a buried barrier PCB board.
[0064] Example 3
[0065] An ultra-thin buried barrier copper foil was prepared according to the preparation process of the ultra-thin buried barrier copper foil in Example 1. The difference from Example 1 is that "the dopamine alkaline solution is a Tris buffer solution containing 2 mg / L dopamine and a pH value of 8.5" is replaced by "the dopamine alkaline solution is a Tris buffer solution containing 1 mg / L dopamine and a pH value of 8", and "the metal plating solution is: 1.4 g / L nickel sulfate, 0.7 g / L zinc sulfate, 3.0 g / L boric acid, 66 g / L potassium pyrophosphate, 28 mg / L sodium saccharin and water, and the pH value of the metal plating solution is 8.4" is replaced by "the metal plating solution is: 1.2 g / L nickel sulfate, 0.6 g / L zinc sulfate, 2.4 g / L boric acid, 60 g / L potassium pyrophosphate, 24 mg / L sodium saccharin and water, and the pH value of the metal plating solution is 8", to obtain an ultra-thin buried barrier copper foil and a buried barrier PCB board.
[0066] Example 4
[0067] The ultra-thin buried barrier copper foil is prepared according to the preparation process of the ultra-thin buried barrier copper foil of Example 1. The difference from Example 1 is that the "copper foil electrolyte is the following components: Cu 2+ 65g / L, sulfuric acid 90g / L, Cl - 6mg / L, 30mg / L of hydrolyzed collagen with a molecular weight of 2000-3000Da and 20mg / L of sodium polydisulfide propane sulfonate; the electrolytic temperature of the electrolytic copper foil deposition electrolyte is 47°C, and the electrolytic current density is 500mA / cm 2 " is replaced by "The copper foil electrolyte is composed of the following components: Cu 2+ 50g / L, sulfuric acid 130g / L, Cl -10mg / L, 40mg / L of hydrolyzed collagen with a molecular weight of 2000-3000Da and 15mg / L of sodium polydisulfide propane sulfonate; the electrolytic temperature of the electrolytic copper foil deposition electrolyte is 43°C, and the electrolytic current density is 300mA / cm 2 ", and obtain ultra-thin buried copper foil and buried PCB board.
[0068] Example 5
[0069] The ultra-thin buried barrier copper foil was prepared according to the preparation process of the ultra-thin buried barrier copper foil of Example 1. The difference from Example 1 is that the resistance value of the required ultra-thin buried barrier copper foil is 25Ω; the resistivity of the resistance layer is 3×10 -5 Ω·m; the position and size of the resistance window (length 2.5mm, width 1.0mm); the copper ion concentration in the etching solution is 90g / L, and the chloride ion concentration is 100g / L; the pH value of the etching solution is 4.0, and the temperature of the etching solution is 50℃" is replaced by "the resistance value of the required ultra-thin buried copper foil (50Ω); the resistivity of the resistance layer is 3×10 -5 Ω·m; the position and size of the resistance window (5 mm in length and 1.0 mm in width); the copper ion concentration in the etching solution is 100 g / L and the chloride ion concentration is 110 g / L; the pH value of the etching solution is 3.0, and the temperature of the etching solution is 45°C", and an ultra-thin buried copper foil and a buried PCB board are obtained.
[0070] Example 6
[0071] The ultra-thin buried barrier copper foil was prepared according to the preparation process of the ultra-thin buried barrier copper foil of Example 1. The difference from Example 1 is that the "resistance plating solution consists of 24 g / L nickel ions, 6 g / L chromium ions, 24 g / L sodium hypophosphite and 22 g / L boric acid; the plating temperature of the resistance plating solution is 50°C, and the plating current density is 300 A / dm 2 " is replaced by "The resistor electroplating solution is composed of 20g / L nickel ions, 4g / L chromium ions, 20g / L sodium hypophosphite and 20g / L boric acid; the electroplating temperature of the resistor electroplating solution is 48°C and the electroplating current density is 400A / dm 2 ", and obtain ultra-thin buried copper foil and buried PCB board. Among them, the resistivity of the resistor layer is 3.17×10 -5 Ω·m, according to the calculation, the film window size is 2.4mm long.
[0072] Example 7
[0073] The ultra-thin buried barrier copper foil was prepared according to the preparation process of the ultra-thin buried barrier copper foil of Example 1. The difference from Example 1 is that the "resistance plating solution consists of 24 g / L nickel ions, 6 g / L chromium ions, 24 g / L sodium hypophosphite and 22 g / L boric acid; the plating temperature of the resistance plating solution is 50°C, and the plating current density is 300 A / dm 2 " is replaced by "The resistor electroplating solution is composed of 30g / L nickel ions, 8g / L chromium ions, 26g / L sodium hypophosphite and 24g / L boric acid; the electroplating temperature of the resistor electroplating solution is 52°C, and the electroplating current density is 150A / dm 2 ", and obtain ultra-thin buried copper foil and buried PCB board. Among them, the resistivity of the resistor layer is 2.90×10 -5 Ω·m, according to the calculation, the film window size is 2.6mm long.
[0074] Comparative Example 1
[0075] An ultra-thin buried barrier copper foil was prepared according to the preparation process of the ultra-thin buried barrier copper foil in Example 1, which differs from Example 1 in that no organic layer was prepared, and an ultra-thin buried barrier copper foil and a buried barrier PCB board were obtained.
[0076] Comparative Example 2
[0077] An ultra-thin buried barrier copper foil was prepared according to the preparation process of the ultra-thin buried barrier copper foil in Example 1, which differs from Example 1 in that no metal layer was prepared, and an ultra-thin buried barrier copper foil and a buried barrier PCB board were obtained.
[0078] Comparative Example 3
[0079] Compared with Example 1, the only difference is that the film unwinding and winding speed is 6 m / min.
[0080] Test example
[0081] The relevant performance characterization results of the ultra-thin buried copper foils of Examples 1-10 and Comparative Examples 1-3 are shown in Table 1.
[0082] Table 1 Characterization of related properties of ultra-thin buried copper foil
[0083]
[0084]
[0085] The results in Table 1 show that compared with Comparative Examples 1-3 and Example 1, the buried copper foil obtained by the preparation method of the present invention has a small roughness and a high resistance value precision per unit area, that is, a high square resistance value precision. The use of a peelable layer composed of an organic layer and a metal layer can significantly reduce the roughness of the buried copper foil and improve the resistance value precision.
[0086] Finally, it should be noted that the above content is only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Simple modifications or equivalent substitutions of the technical solution of the present invention by ordinary technicians in this field do not deviate from the essence and scope of the technical solution of the present invention.
Claims
1. A process for preparing an ultra-thin buried copper foil, characterized in that: The following steps are involved: (1) Pretreatment of carrier copper foil; (2) preparing a peelable layer; the peelable layer comprises an organic layer and a metal layer; the two sides of the organic layer are respectively a carrier copper foil and a metal layer; the organic layer is a polydopamine layer; (3) preparing an ultra-thin buried barrier copper foil; performing electrolytic deposition on the surface of the metal layer to obtain an ultra-thin copper foil layer; performing etching on the ultra-thin copper foil layer and electroplating a resistor layer to obtain an ultra-thin buried barrier copper foil layer after electroplating, and removing the carrier copper foil and the strippable layer to obtain the ultra-thin buried barrier copper foil.
2. The preparation process according to claim 1, characterized in that: The polydopamine layer described in step (2) is obtained by self-polymerization reaction of a dopamine alkaline solution; the dopamine alkaline solution is a Tris buffer solution containing 1-4 mg / L dopamine and a pH value of 8-9.
3. The preparation process according to claim 1, characterized in that: The metal layer described in step (2) is obtained by electroplating a metal plating solution; the metal plating solution comprises: 1.2-1.6 g / L nickel sulfate, 0.6-0.8 g / L zinc sulfate, 2.4-3.2 g / L boric acid, 60-70 g / L potassium pyrophosphate, 24-32 mg / L saccharin sodium and water; the pH value of the metal plating solution is 8-9.
4. The preparation process according to claim 1, characterized in that: The electrolyte for the electrolytic deposition in step (2) comprises the following components: Cu 2+ 50-65g / L, sulfuric acid 90-130g / L, Cl - 6-10 mg / L, 30-40 mg / L of hydrolyzed collagen with a molecular weight of 2000-3000 Da and 15-20 mg / L of sodium polydisulfide propane sulfonate; the electrolytic deposition temperature is 43-47° C.; the electrolytic deposition current density is 300-500 mA / cm 2 .
5. The preparation process according to claim 1, characterized in that: The etching described in step (3) is performed using an etching solution, which contains the following components: 90-110 g / L copper ions and 100-120 g / L chloride ions; the pH value of the etching solution is 2-4, and the temperature of the etching solution is 45-55°C.
6. The preparation process according to claim 1, characterized in that: The electroplating solution described in step (3) includes nickel salt, chromium salt, sodium hypophosphite and boric acid; in the electroplating solution, the concentration of nickel ions in the nickel salt is 20-30 g / L, the concentration of chromium ions in the chromium salt is 4-8 g / L, the concentration of sodium hypophosphite is 20-26 g / L, and the concentration of boric acid is 20-24 g / L; the electroplating temperature of the resistor electroplating solution is 48-52°C; the electroplating current density of the resistor electroplating solution is 150-400 A / dm 2 .
7. The preparation process according to claim 1, characterized in that: Step (3) also includes film unwinding, laminating, peeling and winding; specifically, the film with a window is unrolled and laminated on the surface of the ultra-thin copper foil layer, and then the ultra-thin copper foil layer exposed at the window position of the film is etched and electroplated to obtain the electroplated ultra-thin copper foil layer, the film and the electroplated ultra-thin copper foil layer are peeled off and rolled up, and the carrier copper foil and the peelable layer are removed to obtain the ultra-thin buried barrier copper foil.
8. The preparation process according to claim 1, characterized in that: Step (3) also includes silanization treatment, specifically: silanization treatment is performed on the surface of the ultra-thin buried copper foil layer after electroplating; the silanization treatment uses an organic silane coupling agent; the organic silane coupling agent is selected from one or more of KH550, KH560 and KH570; the concentration of the organic silane coupling agent is 1.0-1.5g / L, and the pH value is 9-12; the temperature of the silanization treatment is 25-35°C.
9. The ultra-thin buried copper foil prepared by the preparation process according to any one of claims 1 to 8, characterized in that: The ultra-thin buried copper foil has a thickness of 3-5 μm, a roughness of the smooth surface of ≤1.5 μm, a square resistance of 20-50 Ω / sq, and a square resistance deviation of less than or equal to 10%.
10. Application of the ultra-thin buried barrier copper foil prepared by the preparation process according to any one of claims 1 to 8 or the ultra-thin buried barrier copper foil according to claim 9 in buried barrier PCB boards.
